Contingent Imitation and Young Children At-Risk for Autism Spectrum Disorder. (June 2019) - Killmeyer, Susan; Kaczmarek, Louise; Kostewicz, Douglas; Yelich, Amy
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by early and pervasive deficits in social orienting and social engagement. Although parent-implemented interventions using a range of responsive interactive techniques have demonstrated effectiveness to increase social engagement, more work is needed to examine how best to support a responsive parental style to increase social engagement in an exceptionally heterogeneous population. Emerging evidence suggests that contingent imitation (CI) may be a uniquely effective way to increase social engagement in children with ASD. This study used a multiple-baseline single case design across participants to examine how three caregivers learned to use CI at home with fidelity with their young children at-risk for or who had ASD. Results demonstrated that parents quickly acquired the accurate use of this simple technique at home. Furthermore, using CI with fidelity, caregivers sharply reduced their use of questions and directives during play. After caregivers were taught the CI procedure, positive changes in child social eye gaze were seen across intervention and maintenance phases. Implications for research and early intervention practice are discussed.